Physician deaths from COVID-19 have been lower than expected - Kaplan, R M (Occup Med (Lond), 2021)
BACKGROUND: More than 100 US physicians have died from COVID-19. I considered the number of US physician deaths in comparison to the expected COVID death rate in the general population. AIMS: To estimate the whether US physicians are at increased risk of death from COVID-19 due to occupational exposures. METHODS: COVID-related physician deaths were identified through searches using Medscape In Memoriam, and multiple internet searches using Google and Facebook. An obituary or death notice was obtained in all but one case. Death rates among physicians were compared to the expected rate based on COVID deaths in the US population. RESULTS: Up to 7 October 2020, there were 108 deaths among US physicians. Physicians make up about 0.33% of the US population. By 1 October 2020, there were 210 000 COVID deaths in the US population with 693 expected physician deaths. Observed deaths were 16% of expected. Seventy-five per cent of the deaths occurred among physicians older than age 60 and about half appeared to be among those retired from clinical practice. CONCLUSIONS: Observed physician deaths were significantly below expected based on deaths the general population. Prudent use of personal protective equipment may explain the lower-than-expected death rates.